TRAVELING TECHNOLOGIES: Infrastructure, Ethical Regimes, and the Materiality of Politics in South Africa - VON SCHNITZLER, ANTINA (Cultural anthropology, 2013)
In this article, I explore the politics of infrastructure in South Africa by focusing on the "travels" of a small technical device. Since the end of apartheid, prepaid meters have been widely deployed in South Africa's townships to curb the nonpayment of service charges. Yet many residents have bypassed their meters, enabling them to illicitly access electricity or water. I track the micro-political battle between residents tinkering with the technology and engineers trying to secure it, arguing that infrastructure itself becomes a political terrain for the negotiation of central ethical and political questions concerning civic virtue and the shape of citizenship. To investigate this techno-political terrain, I trace a genealogy of the meter from Victorian Britain, when it was invented as a tool of working-class "moral improvement,"to the late-apartheid period, when it was reassembled as a device of counterinsurgency against the anti-apartheid "rent boycotts." In each moment, I suggest, the meter was harnessed to distinct ethical regimes and political projects. Drawing on my ethnographic fieldwork with engineers in contemporary South Africa, I explore the semiotic-material work required to make the device functional in the post-apartheid moment. Tracing the travels of a small technical device across time and space, I argue, opens up conceptual space to rethink the relationship between ethics, politics, and technics.